Fatores que influenciam a inadimplência dos financiamentos do Programa Agroamigo no Ceará - Silveira Junior, José Airton da (2012)
This work aims to identify factors that influence the default of loans made by Banco do Nordeste do Brasil (BNB) in Ceará through the rural microfinance program of BNB, the Agroamigo. Thus we investigate individual characteristics, financing, and market activities, and also the condition of recieving the Family Grant Program Bolsa Família. From information collected on socio-economic surveys, we determine the variables that influence the default of loans through a Logit regression model. We conclude that the variables Bolsa Familia, marital status, education, gender, period of funding, timing of plots and antrepreneurship are relevant to the default.